Mola hidatiforme completa invasiva: una causa poco común de hipertiroidismo - Sara Correia; Gustavo Rocha; Maria João Oliveira (Sociedade Galega de Medicina Interna, 2021)
Hydatidiform mole (HM) is a form of gestational trophoblastic disease, which can be classified as complete or partial and is characterized by high levels of human chorionic gonadotropin (HCG). Hyperthyroidism results from the effect of β-hCG on TSH receptors. Clinical case: A 53-year-old multiparous woman, with no relevant history, was admitted to the Gynaecology Emergency Department with a clinic presentation of hypogastralgia and hyperemesis gravidarum with 1 month of evolution and symptoms of hyperthyroidism. The investigation showed a distended uterus with echogenic material with a thickness of 81 mm at filled by uterine cavity. β-hCG> 10000mIU / mL. She was admitted for suction curettage, and the resulting sample was compatible with HM. The additional analytical study showed primary hyperthyroidism and negative thyroid autoimmunity. Thyroid ultrasound was unaltered. The patient started therapy with metibasol and propanolol, showing clinical and analytical improvement. She also underwent, total abdominal hysterectomy and bilateral annexectomy with general anaesthesia, without complications. Chest x-ray without changes. Through histological analysis it was determined that the diagnosis was that of an invasive complete HM. Sixteen weeks after surgery, she presented β-hCG <2mIU / mL and normal thyroid function. The patient is still being monitored in the Gynaecology outpatient consultation. Thyroid function should be included in the laboratory analysis of HM. Removing the source of β-hCG allows the resolution of hyperthyroidism. However, due to the risk of thyroid storm, it is crucial to control the thyroid function before performing the surgical procedure. Given the possibility of persistence of trophoblastic tissue, it is essential to maintain regular follow-up with β-hCG assays.